2005
DOI: 10.1080/01443610500171201
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of family planning amongst community health extension workers in Kaduna State, Nigeria

Abstract: A self-administered opportunistic questionnaire was given to 232 community health extension workers (Chews) in Kaduna state, Nigeria. Seventy-eight were male and 154 female. All could recall at least one modern method of family planning. The oral contraceptive pill (OCP) (85.8%), injectable contraceptives (85.3%), and the intra-uterine contraceptive device (IUCD) (56.0%), were most widely known about. Emergency contraception was not known about. A high percentage of female Chews have practised family planning:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
3
13
0
Order By: Relevance
“…In agreement with our findings, Orji et al reported that religion was found to influence the attitude of married Nigerian men towards family planning (33). Another study by Onwuhafua et al reported the reasons for female health extension workers not using any family planning methods; they were the side effects, not being married, not being sexually active, and religious beliefs (34). There are some studies indicating that there is no statistical association between the practice of family planning and religion (10,17) and a mixed influence of religion on women's contraceptive practices (35).…”
Section: Discussionsupporting
confidence: 81%
“…In agreement with our findings, Orji et al reported that religion was found to influence the attitude of married Nigerian men towards family planning (33). Another study by Onwuhafua et al reported the reasons for female health extension workers not using any family planning methods; they were the side effects, not being married, not being sexually active, and religious beliefs (34). There are some studies indicating that there is no statistical association between the practice of family planning and religion (10,17) and a mixed influence of religion on women's contraceptive practices (35).…”
Section: Discussionsupporting
confidence: 81%
“…As the number of children increases, the proportion of men who agree that the use of family planning is a sin decreases. In the literature, the reasons reported for being opposed to the use of contraception by men were on religious grounds (Mıstık et al, 2003;Mosiur et al, 2008;Onwuhafua, Kantiok, Olafimihan, & Shittu, 2005;Orji, Ojofeitimi, & Olanrewaju, 2007;Srikanthan & Reid, 2008) or the fear of harmful side effects caused by the contraceptives (Mosiur et al, 2008;Onwuhafua et al, 2005) and the desire to have more children (Kolawole et al, 2002;Mosiur et al, 2008;Odu et al, 2005;Tuloro et al, 2006). Similar findings have been found in a number of developing countries.…”
Section: Discussionsupporting
confidence: 70%
“…Approximately 9 in 10 healthcare providers surveyed in Lagos, Nigeria, in 2003 [7] had heard of EC; yet, only one-tenth of them correctly identified the brand, dosage, and appropriate time window for using an ECP regimen. Research [8] conducted among community health workers in Kaduna, Nigeria, uncovered that EC was completely unknown to these professionals.…”
Section: Introductionmentioning
confidence: 98%